Burden of brain and other central nervous system cancer in China, 1990–2019: a systematic analysis of observational data from the global burden of disease study 2019 - Peng Yin; Maigeng Zhou; Fan Zhang; E Wang; Xinran Hou; Zongbin Song; Zhuoyi Liu; Wenyong Long; Zheng Long; Maoen Zhu (BMJ Open)
Objective To evaluate the trends in disease burden and the epidemiological features of central nervous system (CNS) cancer in China from 1990 to 2019.Design A population-based observational study.Setting The incidence, prevalence, death and disability-adjusted life years (DALYs) due to CNS cancer in China, stratified by sex, age and provincial region, were collected from the Global Burden of Disease Study 2019.Participants Data were publicly available and individuals were not involved.Results In 2019, the incident cases of CNS cancer in China were 347 992 (95% UI 262 084–388 896), and the age-standardised rate (ASR) of incidence was 5.69 (95% UI 4.36–6.78) per 100 000 person-years increased by 27.9% compared with that in 1990; meanwhile, CNS cancer caused 63 527 (95% UI 47 793–76 948) deaths in China in 2019, and the ASR of death was 3.5 (95% UI 2.62–4.21) per 100 000 person-years decreased by 9.6%. The ASRs of incidence and prevalence of CNS cancer in China increased more rapidly than the global average; meanwhile, the ASRs of DALYs owing to CNS cancer declined more rapidly. The burden of CNS cancer showed no significant differences between men and women, but was more pronounced in early childhood and old adulthood. The ASRs of incidence and prevalence were higher in high-income provinces, confirmed by the positive correlation with Sociodemographic Index (SDI), with correlation coefficient r of 0.322 and 0.767, respectively (both p<0.0001). However, the ASRs of death and DALYs demonstrated a negative correlation with SDI, with r of -‍0.319 and −0.642, respectively (both p<0.0001).Conclusions From a global perspective, China has been bearing a substantial burden of CNS cancer. More attention should be paid to children and elderly populations for CNS cancer. The disease burden varied significantly at the subnational level of China, which was associated with socioeconomic development.